Simulated microgravity altered the cell cycle progression of porcine granulosa cells - Xuan Dai, Truong; Nghia Son, Hoang; Thanh Long, Le (Vietnam Journal of Biotechnology, 2022)
Microgravity has been shown to markedly affect reproduction in humans and animals, especially reproductive organs such as the ovaries. Granulosa cells are one of the important components of the ovary, playing an important role in supporting oocyte maturation and fertilization. However, the effects of microgravity on granulosa cells have not been well characterized. This study aimed to assess the effects of simulated microgravity (SMG) on the cell cycle progression of porcine granulosa cells (pGCs). The pGCs were induced SMG for 72 h by Gravite® simulator, while cells of the control group were treated in normal conditions. Cell cycle analysis revealed that SMG condition induced an increase of the ratio of pGCs in the G0/G1 phase, leading to the cell cycle arrest phase, while the ratio of pGCs in the G2/M phase was decreased. There was no difference in the cell ratio of the S phase between the control group and the SMG group. Real-time RT-PCR analysis indicated that the expression of cdk4 and cdk6 transcripts of pGCs from the SMG group was lower than the control group. This down-regulation was also observed cyclin A and cyclin D1 transcript expression in pGCs from the SMG group. Immunostaining displayed the lower exhibition of microfilament and microtubule in pGCs from the SMG group comparing to the control group. Western blot analysis showed that the expression of β-actin and α-tubulin was reduced in pGCs from the SMG group. These changes contributed to the alteration of cytoskeletal structure, including microfilaments and microtubules, which affect cell division. These results revealed that the SMG condition induced changes in the cell cycle progression of pGCs.